A novel approach for the removal of radiocesium from aqueous solution by ZSM-5 molecular sieve. (September 2018) - Gao, Xiaoqing; Zhang, Peng; Yang, Junqiang; Sun, Xuejie; Fu, Yi; Shi, Keliang; Chai, Zhifang; Wu, Wangsuo
Abstract: Finding an approach for pretreatment of radionuclides from contaminated water are interesting topics of research. In present work, the ZSM-5 molecular sieve was characterized with different techniques such as zeta potential, SEM, FT-IR and XRD to clarify the surface properties of sample and applied as a sorbent to concentrate and recover Cs(I) from aqueous solution. The effect of environmental conditions such as contact time, ionic strength, content of sorbent and solution pH on Cs(I) uptake were optimized using batch techniques. Different kinetic and isotherm models were utilized to evaluate the experimental data and the correlation parameters were obtained. Based on the sorption/desorption experiment, it can be deduced that the ZSM-5 molecular sieve has potential application for the rapid and quantitative recovery of radiocesium from wastewater. Highlights: Comprehensive evaluation the environmental parameters which affect the sorption abilities of Cs(I) by ZSM-5 molecular sieve; The sorption kinetics as well as isotherm of Cs(I) were investigated through modeling evaluation. The desorption of Cs(I) from ZSM-5 molecular sieve was carefully studied. A novel approach for the rapid and quantitative recovery of radiocesium from wastewater was proposed.